The unexplored links between soil, soil biodiversity, and soil-related ecosystem services - Janina Kleemann; Bastian Steinhoff-Knopp; Nico Eisenhauer; Christian Ristok; Willi E. R. Xylander; Benjamin Burkhard (Soil Organisms)
Soil and its biotic and abiotic components have a huge impact on human well-being, but, on the other hand, they are often neglected in scientific studies or by policy and society in comparison to other ecosystem components. In this study, we provide an overview of the direct and indirect positive and negative influences of soil and soil biodiversity (SBD) on the supply of regulating, provisioning, and cultural (soil-related) ecosystem services. We selected Germany as an example of a well-funded country for research, but we found only a small collection of described and analyzed interactions between SBD and soil-related ecosystem services considering the huge amount of species in the soil. Positive effects of SBD on soil-related ecosystem services in Germany were especially found for the regulation of soil quality and, therefore, the potentially positive impacts on plant cultivation. In addition, interactions between soil, SBD, and cultural ecosystem services were documented, for example, for physical and emotional interactions, aesthetic, soil as an archive, soil as a habitat for species, and soil for education and science. No publications on national and international level were found, for example, on the negative influence of SBD on the cultural ecosystem services tourism / recreation, spiritual interactions, entertainment, and non-use values which underlines the dominance of positively documented interactions. Even though the analyses of causal interdependencies in the nexus between soil, SBD, and soil-related ecosystem services might be challenging due to its complexity, more comprehensive assessments of this nexus should be encouraged.